Інформаційні канали як розвиток уявлень про канали зв’язку - Diduk, N. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The general notion of information channel is built, which represents an extension of the notions of a communication channel (information theory) and transitional probability distribution (probability theory) to all the types of uncertainty. The examples of information channels, including ideal and fictitious ones are presented. Three main applications of information channels are considered.